2008
DOI: 10.1080/15295190701830672
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Social Risk, Parenting, and Infant Development in Rural Low-Income Communities

Abstract: SynopsisObjective-The extent to which the severity of exposure to social risk is related to parenting and cognitive development in the first 15 months of an infant's life was studied in a representative diverse sample of families in two rural poor regions in the United States.Design-One thousand two hundred ninety-two families were followed for the first 15 months of the infant's life.Results-Evidence supported a pathway from risk severity through maternal sensitivity and warmth, language and learning activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(139 citation statements)
references
References 50 publications
7
127
0
5
Order By: Relevance
“…These studies show that cognitive outcomes worsen as the number of adversities increases. This gradient has been observed from infancy through adolescence for outcomes of general cognitive ability (8,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). For executive functioning, this gradient has been observed for attention at ages 3-4 y (33,34), self-regulation at 3 y (35), and delay of gratification at 8-10 y (36).…”
Section: Salient Adverse Experiences and Cognitive Developmentmentioning
confidence: 86%
“…These studies show that cognitive outcomes worsen as the number of adversities increases. This gradient has been observed from infancy through adolescence for outcomes of general cognitive ability (8,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). For executive functioning, this gradient has been observed for attention at ages 3-4 y (33,34), self-regulation at 3 y (35), and delay of gratification at 8-10 y (36).…”
Section: Salient Adverse Experiences and Cognitive Developmentmentioning
confidence: 86%
“…[32] Poorer quality parent-child interactions, in turn, have been associated with depressed child cognitive development. [24,33] Trauma-induced psychological symptoms (e.g., posttraumatic stress disorder [PTSD]) may contribute to cognitive deficits by impeding the ability to engage the environment effectively and learn new skills. [3] Some studies have found that neural/cognitive effects from trauma exposure are evident only among participants with PTSD, whereas others have documented effects regardless of psychiatric status.…”
Section: Discussionmentioning
confidence: 99%
“…Sameroff and others (Sameroff, Seifer, Barocas, Zax & Greenspan, 1987), for example, have found that the presence of risk factors significantly increases the probability of negative outcomes. Additive relationships between risk factors and children's outcomes have been found in studies examining infants' development (Burchinal, Vernon-Feagans & Cox, 2008), parenting and temperament in toddlers (Popp, Spinrad & Smith, 2008), and violent behaviors among adolescents . Evidence also suggests that accumulations of risk beginning in childhood may have longlasting consequences, as demonstrated in a longitudinal study of children with depressive and anxiety disorders (Stansfeld, Clark, Rodgers, Caldwell & Power, 2011).…”
Section: Risk and Promotive Factorsmentioning
confidence: 99%